Upaya penambahan pendapatan keluarga dengan budidaya ikan teknologi sederhana di Kelurahan Binawidya Kecamatan Binawidya Pekanbaru - Iskandar Putra; Rusliadi Rusliadi; Romie Jhonnerie; T. Ersti Yulika Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The Covid-19 outbreak has a global impact, especially in terms of the community's economy, so that those affected by this outbreak find it difficult to finance their daily needs, therefore efforts are needed to increase people's income. One technology that can be applied is the cultivation of fish in tanks with vegetables (aquaponics). The purpose of this activity is to provide knowledge and skills about the cultivation of catfish (Clarias gariepinus) with aquaponics technology of the bucket fish farming system which can ultimately be used as additional income, besides that it is hoped that this activity can be used as an example in updating/information in the field of aquaculture. This socialization activity was carried out in the